2013
DOI: 10.1177/1352458513495938
|View full text |Cite
|
Sign up to set email alerts
|

Role of intravenous immunoglobulin in the treatment of acute relapses of neuromyelitis optica: experience in 10 patients

Abstract: Prompt treatment of neuromyelitis optica (NMO) relapses with steroids or plasma exchange (PLEX) often prevents irreversible disability. The objective of this study is to report the use of intravenous immunoglobulins (IVIG) as treatment for acute relapses in NMO. A retrospective review of 10 patients treated with IVIG for acute relapses was conducted. IVIG was used in the majority of cases because of lack of response to steroids with/without PLEX. Improvement was noted in five of 11 (45.5%) events; the remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 8 publications
1
70
0
5
Order By: Relevance
“…The benefit of IVIg in acute demyelinating attacks is limited to case reports and small case series [49][50][51][52][53], and is thought to provide benefit by directly affecting cytokine production and T-cell proliferation and by binding potential autoantibodies targeted against myelin [54,55]. IVIg is given at a dose of 2 g/kg divided over 2-5 days.…”
Section: Acute Management Of Demyelinating Attacksmentioning
confidence: 99%
“…The benefit of IVIg in acute demyelinating attacks is limited to case reports and small case series [49][50][51][52][53], and is thought to provide benefit by directly affecting cytokine production and T-cell proliferation and by binding potential autoantibodies targeted against myelin [54,55]. IVIg is given at a dose of 2 g/kg divided over 2-5 days.…”
Section: Acute Management Of Demyelinating Attacksmentioning
confidence: 99%
“…These studies show the effect of IVIG in preventing NMO relapses. A recent study demonstrated that IVIG achieved visual improvement in 5 of 11 (45.5 %) optic neuritis cases in the acute phase [9]. That study concludes that IVIG could be an option in treating NMO relapses.…”
Section: Introductionmentioning
confidence: 95%
“…A retrospective study examining IVIG as an attack therapy in patients nonresponsive to IVMP with or without TPE revealed beneficial effects in 5/11 attacks [53]. Two randomized controlled trials are currently evaluating the efficacy of IVIG for NMOSD attacks.…”
Section: Treatment Of Nmosd Attacksmentioning
confidence: 99%